2015
DOI: 10.1080/10408398.2013.816653
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Reporting of Dietary Assessment Methods in Food-based Randomized Controlled Trials over a Ten-year Period

Abstract: The importance of monitoring dietary intake within a randomized controlled trial becomes vital to justification of the study outcomes when the study is food-based. A systematic literature review was conducted to determine how dietary assessment methods used to monitor dietary intake are reported and whether assisted technologies are used in conducting such assessments. OVID and ScienceDirect databases 2000-2010 were searched for food-based, parallel, randomized controlled trials conducted with humans using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 282 publications
(203 reference statements)
0
8
0
Order By: Relevance
“…Relatively few studies were found and included in this review, limiting the conclusions that can be drawn between dietary intakes and symptoms. The lack of a standardised approach to dietary assessment methods with respect to those included studies in which primary outcome measures related to food measurement limited any comparison between studies, and this issue has been identified previously in the dietary methodology literature, even in relation to food‐based randomised trials . However, the present review used a standardised approach, which included a published methodology, searching a variety of online databases, assessed study quality using recognised tools and was completed in accordance with the PRISMA statement .…”
Section: Limitationsmentioning
confidence: 99%
“…Relatively few studies were found and included in this review, limiting the conclusions that can be drawn between dietary intakes and symptoms. The lack of a standardised approach to dietary assessment methods with respect to those included studies in which primary outcome measures related to food measurement limited any comparison between studies, and this issue has been identified previously in the dietary methodology literature, even in relation to food‐based randomised trials . However, the present review used a standardised approach, which included a published methodology, searching a variety of online databases, assessed study quality using recognised tools and was completed in accordance with the PRISMA statement .…”
Section: Limitationsmentioning
confidence: 99%
“…Being able to complete the app-based task at home on a smartphone possibly offset the impact of participants wanting to provide socially desirable responses during the interviews. The increasing use of this methodology in food-based research studies reflects the shift toward patient-oriented data capture, as daily diaries may help monitor changes in eating behaviors over time [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical research settings, open-ended dietary assessment methods such as food records and diet history interviews tend to be used to generate dietary intake data [8]. The data is generated by a stepwise process including collection and coding [9].…”
Section: Introductionmentioning
confidence: 99%